Upaya Guru dalam Meningkatkan Pemahaman Peserta Didik tentang Materi Transformasi dengan Menguatkan Materi Prasyarat pada Mata Pelajaran Matematika - Winanto, Awan (Journal of Innovation in Teaching and Instructional Media, 2022)
This study aims to determine the teacher's efforts in increasing students' understanding of the transformation material by strengthening the prerequisite material in mathematics. The approach used in this study refers to the principles of descriptive analysis research. Data collection techniques used in this study were interviews, observation, and documentation. The results of the study indicate that teachers have many important roles that must be carried out in learning activities. The teacher's role in learning mathematics is to prepare learning by simplifying the material, facilitating students to learn by making teaching materials and learning media, organizing tasks that will be given to students and conducting assessments.